Digital light processing of SiC ceramic from allylhydridopolycarbosilane with limited acrylate monomers. Issue 13 (1st July 2022) - Gong, Jian; Wang, Yuanjie; Huang, Jing; Pei, Xueliang; He, Liu; Huang, Zhengren; Song, Yujie; Huang, Qing
Abstract: Digital light processing of ceramic precursor was used to prepare SiC rich ceramic parts in this study. In order to achieve appropriate light curing rate, the ceramic precursor allylhydropolycarbosilane (LHBPCS) was mixed with acrylate monomers tripropylene glycol diacrylate and trimethylolpropane triacrylate. The content of acrylate monomers was optimized to increase the ceramic yield and reduce the shrinkage during pyrolysis. According to the results of thermogravimetric analysis and photolithography experiment, 15 wt% acrylate monomers was appropriate. 330 mJ/cm 2 UV irradiation dose was selected for every layer with a thickness of 25 μm, and green bodies with different shapes were successfully printed. During pyrolysis, these printed parts changed from transparent yellow to black accompanying uniform shrinkage. At 1000 °C, the shrinkage was 24.0–26.0%, and crack-free SiC rich ceramic parts with density of 2.11 g/cm 3 and chemical formula of SiC1.31 O0.26 were obtained.